From National Strategy to Local Reality: A Framework for Effective E Government in Indonesia’s Decentralized Bureaucracy - Pasaribu, M. Irvan Yazid; Rojikinnor; Malizal, Zelynda Zeinab (Indonesian Scientific Publication, 2024)
This study investigates the institutional and infrastructural challenges affecting the implementation of e government in Indonesia within the context of administrative decentralization. Over the past decade, Indonesia has significantly improved its E Government Development Index (EGDI), rising from 0.45 in 2016 to 0.72 in 2022. Despite national level progress, regional disparities persist, driven by institutional fragmentation, limited human capital, and uneven ICT infrastructure. The objective of this study is to examine these constraints and offer a conceptual framework for addressing them. Using a qualitative descriptive approach, the study draws on secondary data from UN EGDI reports, national regulations, and case studies such as North Barito and urban–rural comparisons. The research utilizes thematic and comparative analyses to identify patterns in policy disconnection, leadership gaps, and citizen participation. Findings reveal that institutional coherence, participatory governance models, and adaptive leadership significantly influence successful e government implementation. Integrated policy models, such as Whole of Government and Interoperable Digital Government Frameworks, improve alignment between national strategies and local applications. Additionally, participatory design and feedback loops are essential for increasing service quality and trust. The study concludes that Indonesia’s path forward requires not only technological investment but also structural and cultural reforms. This includes capacity building for public servants, equitable infrastructure development, and inclusive digital engagement mechanisms. The insights gained have broader implications for other decentralized states aiming to advance digital transformation through coordinated, participatory, and context sensitive governance models.